## Solving the Equation: 0.5y - 1 - (2y + 4) = y

This article will guide you through solving the equation **0.5y - 1 - (2y + 4) = y**. We will break down each step to ensure clear understanding.

### Step 1: Simplify the equation

Begin by simplifying the left side of the equation by removing the parentheses and combining like terms.

**0.5y - 1 - (2y + 4) = y****0.5y - 1 - 2y - 4 = y****-1.5y - 5 = y**

### Step 2: Isolate the variable

The goal is to get all the terms with 'y' on one side of the equation and the constant terms on the other side.

**-1.5y - 5 = y****-1.5y - y = 5****-2.5y = 5**

### Step 3: Solve for 'y'

Divide both sides of the equation by -2.5 to isolate 'y'.

**-2.5y = 5****y = 5 / -2.5****y = -2**

### Solution

Therefore, the solution to the equation **0.5y - 1 - (2y + 4) = y** is **y = -2**.